2011
DOI: 10.1366/10-06081
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Monitoring of Diamond Metalization

Abstract: The ultra-high-vacuum growth of thin chromium and aluminum films on single diamond crystals at various temperatures was monitored by means of infrared spectroscopy, which provides instant information on electronic and morphological properties of the produced metal films. In accordance with atomic force microscopy results, spectra for Al indicate a clear island-like growth in the beginning followed by a transition to a continuous layer. Cr growth results in much smoother films because of a special growth mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…On the basis of the analysis of the slope according to ref we conclude that the plasma frequencies of all nanoscaled materials are similar, except for iron. The same is obtained in literature: the values of the materials aluminum (77 700 cm –1 ), copper (66 000 cm –1 ), gold (67 900 cm –1 ), and silver (71 800 cm –1 ) are similar, whereas the value for iron (35 200 cm –1 ) points out a significantly lower plasma frequency. Note that for aluminum, there is a significant mismatch with other literature values (e.g., 119 000 cm –1 ) .…”
Section: Results and Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…On the basis of the analysis of the slope according to ref we conclude that the plasma frequencies of all nanoscaled materials are similar, except for iron. The same is obtained in literature: the values of the materials aluminum (77 700 cm –1 ), copper (66 000 cm –1 ), gold (67 900 cm –1 ), and silver (71 800 cm –1 ) are similar, whereas the value for iron (35 200 cm –1 ) points out a significantly lower plasma frequency. Note that for aluminum, there is a significant mismatch with other literature values (e.g., 119 000 cm –1 ) .…”
Section: Results and Discussionsupporting
confidence: 85%
“…In literature, there are many publications available, reporting Drude parameters (electronic scattering rate ω τ , plasma frequency ω p , and dielectric background ε ∞ ) of metal films. It was found that for the very same material, these parameters dramatically vary for thin films as well as for different morphologies, as it was shown by Fahsold et al in the example of iron. For the analysis of the plasmonic properties of the nanoantenna arrays in the IR, it is important that in the range below 2000 cm –1, the metals under investigation can be well-described by the Drude model.…”
Section: Results and Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…For randomly grown island films, the distribution of particle size and distance broadens the infrared spectrum significantly; thus it looks like a smooth background in infrared transmittance. The slope of that background is determined by the density of the particles and changes its sign at the percolation threshold; see Figure .…”
Section: Nonresonant Surface-enhanced Infrared Absorptionmentioning
confidence: 99%